2013
DOI: 10.1038/jcbfm.2013.79
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Brain Deoxyglucose Uptake and Metabolism by Glucocest MRI

Abstract: 1,4,52-Deoxy-D-glucose (2DG) is a known surrogate molecule that is useful for inferring glucose uptake and metabolism. Although 13 C-labeled 2DG can be detected by nuclear magnetic resonance (NMR), its low sensitivity for detection prohibits imaging to be performed. Using chemical exchange saturation transfer (CEST) as a signal-amplification mechanism, 2DG and the phosphorylated 2DG-6-phosphate (2DG6P) can be indirectly detected in 1 H magnetic resonance imaging (MRI). We showed that the CEST signal changed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
201
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(211 citation statements)
references
References 44 publications
6
201
2
2
Order By: Relevance
“…Consequently, most applications on human brain tumors are focused on mobile proteins and polypeptides, measuring either their concentrations or tumor environmental changes which can modify the exchange rate (Zhou et al 2003a;Togao et al 2014). Amino and hydroxyl protons usually fall in the slow to medium exchange regime (Δω/k exchange ~ 1), but it has been shown that glucose and glycogen can be detected with CEST in animal models at high magnetic field strengths (>9 T, (Chan et al 2012;Nasrallah et al 2013;van Zijl et al 2007)). Recently it was proposed that spin-locking (SL) techniques are more suited for the intermediate exchange regime (Lin et al 2011;Jin et al 2012) and pilot studies could detect myoinositol (Haris et al 2011) and glutamate (Cai et al 2012) using this method.…”
Section: Cest Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, most applications on human brain tumors are focused on mobile proteins and polypeptides, measuring either their concentrations or tumor environmental changes which can modify the exchange rate (Zhou et al 2003a;Togao et al 2014). Amino and hydroxyl protons usually fall in the slow to medium exchange regime (Δω/k exchange ~ 1), but it has been shown that glucose and glycogen can be detected with CEST in animal models at high magnetic field strengths (>9 T, (Chan et al 2012;Nasrallah et al 2013;van Zijl et al 2007)). Recently it was proposed that spin-locking (SL) techniques are more suited for the intermediate exchange regime (Lin et al 2011;Jin et al 2012) and pilot studies could detect myoinositol (Haris et al 2011) and glutamate (Cai et al 2012) using this method.…”
Section: Cest Methodsmentioning
confidence: 99%
“…An increased uptake of glucose in PET is a typical finding in malignant brain tumors. First results indicate that glucose concentrations can be detected by CEST via the hydroxyl protons (glucoCEST) (Nasrallah et al 2013). Significant enhancement of the glucoCEST signal has been found upon systemic glucose infusion in an experimental study with breast cancer cells (Chan et al 2012).…”
Section: Cest Imaging In Brain Tumorsmentioning
confidence: 97%
See 1 more Smart Citation
“…apoptotischen und/oder nekrotischen Tumorarealen und aktivem Tumor mög-lich [41]. Nach intravenöser Applikation von Glukose kann mit CEST-(glucoCEST-)ähnlicher FDG-PET eine nichtinvasive Evaluation des Gewebsglukosestoffwechsels vorgenommen werden [42]. Es sind jedoch weitere Studien notwendig, um das wahre Potenzial der CEST-Bildgebung in der Mammadiagnostik zu erforschen.…”
Section: Chemical-exchange-saturationtransfer(cest)-bildgebungunclassified
“…saturation intensity, offset and duration), it is possible to probe different exchanging protons. CEST offers the possibility to detect metabolites such as glutamate 91 , glucose 92,93 and myo-inositol 94 . These endogenous molecules can be used to explore energy metabolism in ND as non-invasive biomarkers, as they are involved in many biological pathways.…”
Section: Principles Of Functional Mrimentioning
confidence: 99%